Implementation of a Web-Based Student and Teacher Attendance System With QR Code Integration using the RAD - Ganesh Lindung Nusantara; Rian Andrian; Nuur Wachid Abdulmajid (INOVTEK Polbeng - Seri Informatika, 2025)
This study aims to implement a web-based student and teacher attendance system with QR Code integration at SMK Muhammadiyah Campaka, Purwakarta. Currently, the school still uses a manual attendance system that is proven to be inefficient, time-consuming, prone to human error, and difficult to monitor in real-time. The proposed system is expected to overcome these problems by increasing the efficiency of managing and monitoring student attendance data. The Rapid Application Development (RAD) approach is used in developing this system, which allows for a faster and more flexible development process. QR Code was chosen as the attendance method because it can speed up attendance recording and reduce data input errors. The results showed that the new system succeeded in reducing attendance recording time by 50%, from an average of 10 minutes to only 5 minutes per class. In addition, the recording error rate was reduced by more than 70%, from the previous 36% to only 9% after the system was implemented. This system also allows attendance reports that can be accessed in real-time, supporting increased efficiency in the school environment. With the implementation of this system, it is hoped that the attendance process will be faster, more accurate, and easier to monitor, which in turn can improve the quality of education management at SMK Muhammadiyah Campaka.